THE USE OF SPATIAL MODELING TO TEACH ENGINEERING GRAPHICS - DÎNTU, Sergiu; ȘULETEA, Angela; BOTEZ, Alexei; JANDÎC, Tudor (Journal of Social Sciences)
The article addresses the problem of increasing the efficiency of studying the object of Engineering Graphics within the limits of the hours stipulated in the curriculum. The student receives at each practical lesson an individual graphic work to apply the theoretical material. They have to create flat drawings after intuitive axonometric drawings. These orthogonal drawings form the basis of the technical documentation. Based on the experience of teaching the discipline, the authors considered it opportune to use the spatial models of the individual task created by the students themselves. A staggered teaching method of 3D modeling was elaborated with the selection of a minimum set of commands necessary for the realization of the proposed model at each of the practical lesson. Students can see the relationship between real objects and their projections, get acquainted with spatial modeling and develop spatial imagination. The analysis of the results implementation of the given method increased the quality of studies.